(untitled) (Bangladesh Journal of Botany, 2026)
The present study identified the pathogenic fungus causing wilt disease in black cumin through morphological, molecular, and pathogenicity analyses, and evaluated in vitro and in silico disease management strategies. The isolated fungus produced white to pink colonies with septate, branched, woolly mycelia; obovoid, aseptate microconidia; and slightly curved macroconidia with 3-4 septa. Molecular identification based on the ITS region (507bp) confirmed the pathogen as Fusarium chlamydosporum (GenBank Accession No. PP002077.1), supported by phylogenetic analysis using the neighbor-joining method. Rovral TS 26WP and Tilt 250EC completely inhibited fungal growth, while Trichoderma harzianum and T. erinaceum showed strong antagonistic activity. Molecular docking identified the phytocompound epoxy azadiradione with the highest binding affinity, a stability further validated by 100 ns Molecular Dynamics simulations. These results suggest that epoxy azadiradione may serve as a promising lead compound for future antifungal development and need further validation through experiments. This is the first report of F. chlamydosporum causing wilt on black cumin in Bangladesh, and it introduces a pioneering combined in vitro and in silico framework for managing this emerging fungal disease. Bangladesh J. Bot. 55(2): 387-394, 2026 (June)